Behaviour in Cornelia de Lange syndrome: a systematic review. (18th December 2016) - Mulder, Paul A; Huisman, Sylvia A; Hennekam, Raoul C; Oliver, Chris; van Balkom, Ingrid D C; Piening, Sigrid
Abstract : Aim: Careful study and accurate description of behaviour are important to understand developmental challenges for individuals with Cornelia de Lange syndrome (CdLS). Here we present a systematic review of current understanding of behaviour in CdLS. Method: A systematic search was performed for articles published between January 1946 and December 2015 evaluating autism, self‐injury, and/or cognition in CdLS. After study‐selection, 43 papers were included. The Cochrane quality criteria were adjusted to assign quality scores to the included studies. Results: Participants were mostly categorized in the severe/profound developmental level. Methodology and quality were very heterogeneous, as well as reporting occurrence of autism. Self‐injurious behaviour was reported in 15 papers. Physical conditions were reported in 21 studies, mostly related to hearing and vision. Only nine studies mentioned details about medication. Interpretation: Comparison of presented results was hindered by heterogeneous assessment methods. Improving our understanding of behavioural characteristics in CdLS requires more uniform methodology. We propose a criterion standard of instruments that can ideally be used in assessment of behaviour and development. This will improve understanding of behaviour in the context of developmental level and daily functioning. What this paper adds: Improving understanding of behaviour in Cornelia de Lange syndrome requires more uniform methods and quality. Combining a survey approach with direct in‐person assessments is necessary. A criterion standard of assessment methods is presented.